VIDEO ASSISTED THORACOSCOPIC SURGERY (VATS); TWO YEARS EXPERIENCE AT THORACIC SURGERY DEPARTMENT, COMBINED MILITARY HOSPITAL RAWALPINDI: Video Assisted Thoracoscopic Surgery - ., Dr Najam Uddin; Majeed, Farhan Ahmed; ., Bilal Umair; Hanif, Muhammad Shoaib; ., Adeel Wayen; ., Kamran Raheem (Pakistan Armed Forces Medical Journal, 2013)
Objective: To review the experience of video-assisted thoracoscopic surgery (VATS) with 202 different cases focusing on indications, operative procedures, side effects and complications.Study Design: Descriptive Study.Place and Duration of Study: Department of Thoracic Surgery, Combined Military Hospital, Rawalpindi, for 2 years from January 2009 till January 2011.Patients and Methods: Two hundred and two video-assisted thoracoscopic surgeries (VATS) were performed over 2 years. There were 131 (64.9%) males and 71(35.1%) female patients.Results: Total two hundred and two patients were selected who were divided into two groups: diagnostic and therapeutic group. The mean age of the patients was 40.25 years (SD ± 12.58) with an age range of 13-77 years. There were 131 males (64.9%) and 71 (35.1%) females. The main indications of video-assisted thoracoscopic surgery were diagnostic in 118 patients and therapeutic in 84 patients. Sixty one patients underwent VATS for indeterminate pleural effusion and a definitive diagnosis was made in 90.2% patients. Definitive diagnosis was made in all sixty six patients who underwent VATS for wedge resection/forceps biopsy of pulmonary nodules, mediastinal masses and interstitial lung disease. VATS thymectomy was performed on 13 patients while 3 patients underwent VATS sympathectomy. Conversion to thoracotomy was required in 8.4% (17/202) of the patients. Adhesions were the most common indication of conversion. There was no operative mortality. The overall median duration of chest tube drainage was 4 days and median postoperative hospital stay was 5 days. Postoperative complications were encountered in 5.9% patients (12/202 patients). No perioperative mortality was encountered in either group.Conclusions: This review indicates that VATS can be performed with minimal morbidity for therapeutic purposes as a current approach for thoracic surgery. It is a safe procedure in many intrathoracic diseases and is associated with less postoperative pain and hospital stay than open thoracotomy.